2014
DOI: 10.1002/j.1532-2149.2013.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in paediatric chronic pain and its impact on depression and functional disability

Abstract: Insomnia is highly important in explaining depression and functional disability in paediatric chronic pain and can be adequately assessed using the ISI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…Data collection began in 2009 and ended in 2012. Pre-treatment assessments from study participants were included as part of previously-reported cross-sectional studies [19,20]. This clinical pilot trial was not registered.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection began in 2009 and ended in 2012. Pre-treatment assessments from study participants were included as part of previously-reported cross-sectional studies [19,20]. This clinical pilot trial was not registered.…”
Section: Methodsmentioning
confidence: 99%
“…The regional ethical review board in Stockholm (Regionala etikprovningsnamnden i Stockholm; FE 289; 171 77; Stockholm, Sweden) approved of the study and participants provided written and informed consent. Assessments of the children were also collected, and analyses and results based on these assessments have been previously reported [20,21]. In brief, most children reported multisite pain (76%), the mean pain duration was four years, the majority of the children were girls (72%), and the mean age was 14 years ( SD = 2.64).…”
Section: Methodsmentioning
confidence: 99%
“…Some data from this sample have been published previously in a paper addressing insomnia in children with chronic pain and as part of the validation of the PII (Kanstrup et al, 2014; Holmstrom et al, 2015). Both parent and child gave informed written consent and the study was approved by the Regional Ethical Review Board in Stockholm.…”
Section: Methodsmentioning
confidence: 99%